Lessons from the Russian Invasion of Ukraine in 2022: Moving the World Beyond War - Ketan Patel; Christian Hansmeyer (Cadmus, 2022)
Russia’s aggression in Ukraine has shaken the post-war liberal order, originally designed to prevent war in Europe and between advanced industrialised countries. While the mechanisms to avoid drawing neighbouring countries (and their allies) into the conflict appear to be holding, the risk of further escalation between Russia and NATO remains considerable. With deterrence, pre-emption and negotiation having failed, Western efforts have now shifted to actions that apply pressure for Russia to cease hostilities and withdraw all forces from Ukraine. The US and its allies have firmly ruled out direct military intervention, leaving escalating economic sanctions as the primary tool with which to respond to Russia’s actions. While the package of sanctions in place to date is unprecedented (and continuing to expand) it remains unclear whether it will compel Russia to negotiate before achieving a military victory in Ukraine. Regardless of Russian military’s success or failure, or the shape of the eventual compromise the parties may reach, the current crisis provides a number of observations and lessons with deep implications for both the parties involved and for the wider global order. If the world is to pre-empt future bloodshed and move conflicts without war, it will need to learn these lessons and create highly effective penalties on regimes as a deterrence against violence.